SISTEM KEPERCAYAAN PAGANISME MASYARAKAT ARAB PRA ISLAM - Damayanty, Rizka; Ellya Roza, Ellya Roza (LP2M IAI Muhammadiyah Bima, 2024)
The aim of writing this article is to find out about the life of Arab society before Islam came. The belief system adhered to by Arab society at that time and how Arab society worshiped by worshiping idols. Arab society before Islam came, was famous for worshiping idols, namely having many gods or gods. The worship of idols is known as